2001
DOI: 10.1002/1098-2736(200102)38:2<159::aid-tea1002>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Student and teacher questioning during conversations about science

Abstract: This paper summarizes case studies developed by a group of collaborating educators. We investigated ways of speaking that encourage students to (a) formulate insightful questions about science topics and (b) express their own ideas during re¯ective discussions. The authors include elementary, high school, and college faculty. Subject-matter contexts included phases of the moon, motion, electricity, light, and waves. In developing case studies, we documented and interpreted student and teacher questions during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(59 citation statements)
references
References 36 publications
3
44
0
6
Order By: Relevance
“…Another social aspect of teaching which has been studied is the 'neutral acknowledgment' of pupil responses to foster pupils' exploration of different points of view and to encourage pupils to keep talking (van Zee, Iwasyk, Kurose, Simpson, & Wild, 2001). These non-evaluative, neutral and supportive features of question-based discourse are perhaps the most accessible practices of dialogic teaching and are a focal point of the study reported here too.…”
Section: Introductionmentioning
confidence: 99%
“…Another social aspect of teaching which has been studied is the 'neutral acknowledgment' of pupil responses to foster pupils' exploration of different points of view and to encourage pupils to keep talking (van Zee, Iwasyk, Kurose, Simpson, & Wild, 2001). These non-evaluative, neutral and supportive features of question-based discourse are perhaps the most accessible practices of dialogic teaching and are a focal point of the study reported here too.…”
Section: Introductionmentioning
confidence: 99%
“…Research carried out in collaboration with practicing teachers has also been similarly productive (e.g. van Zee, Iwasyk et al 2001). In my own work with teachers (Wells 1999;, like Brown and colleagues, and inspired by Dewey (1938) as well as by Vygotsky, we have come to see inquiry as the key element in creating a community of learners.…”
Section: Resultsmentioning
confidence: 90%
“…Oleh karena itu, pertanyaan-pertanyaan arahan dikembangkan dalam rangka untuk menyempurnakan tujuan yang telah disebutkan di atas karena dengan mengajukan pertanyaan yang di desain sedemikian rupa sehingga dapat mengembangkan pemahaman konseptual, kita membuat siswa berpikir. Pertanyaan-pertanyaan tersebut dimaksudkan untuk membantu siswa menjelaskan makna, mengeksplorasi berbagai sudut pandang secara netral dan hormat serta memantau diskusi dan pemikiran mereka sendiri (VanZee et al, 2001) Sebelum melakukan penelitian, dalam sesi wawancara terbuka dengan beberapa siswa, peneliti menyadari bahwa banyak dari mereka yang kurang meminati mata pelajaran fisika yang selama ini diikutinya. Sementara dari hasil penelitian McFarland (2005) menyebutkan bahwa banyak siswa berkomentar sangat positif tentang pembelajaran demonstrasi, seperti demonstrasi membantu pemahaman konsep dan demonstrasi membuat fisika menyenangkan.…”
Section: Pendahuluanunclassified